2012
DOI: 10.1021/jf303256r
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Molecular Modeling Study on Antibody Recognition of Small Molecules: An Immunoassay for Triazine Herbicides

Abstract: Most immunoassays for determination of small molecules are still designed on the basis of the "trial and error" method, due to the lack of understanding of antibody recognition. In the present study, we developed a heterologous indirect competitive enzyme-linked immunosorbent assay for determination of triazine herbicides, with limits of detection for 11 triazines ranging from 0.05 to 29.4 μg/L. Mechanisms of the antigen-antibody interaction were studied by computer-aided molecular modeling (CAMM)-based quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The immunoassay determination of triazines is much easier, less expensive, highly sensitive and rapid. Due to its selectivity and simplicity the immunoassay has been used to detect a wide variety of environmental pollutants including triazines [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoassay determination of triazines is much easier, less expensive, highly sensitive and rapid. Due to its selectivity and simplicity the immunoassay has been used to detect a wide variety of environmental pollutants including triazines [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative structure-activity relationship (QSAR) is widely used studying the immune recognition of diffferent classes of toxic food contaminants, veterinary drugs, including pesticides, etc [11][12][13][14]. The work by Yuan and co-authors reported about an immunoassay analysis of triazines, yet on a small set of 11 compounds [9]. QSAR is used for the analysis of immunoassays on quinolones and fluoroquinolones [15][16][17][18][19], organophosphorus pesticides [20][21], phenylurea herbicides [22], sulfonamides [23].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The most widely used QSAR methods are traditional two-dimensional QSAR (2D-QSAR) based on the Hansch method and three-dimensional QSAR (3D-QSAR), such as comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA). 13 Those approaches showed great power in cross-reactivity (CR) prediction 14,15 , explanation 3, 16, 17 , hapten design 18 and hapten-antibody recognition 2,3,19 . Although there were several QSAR studies carried out on antigen-antibody interaction studies, 13 recognition between chiral hapten and sterospecific antibody has not been seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…142Garcia et al (2015). 143Yuan et al (2012),Mulyanto (2011), Hanasaki et al (2008,Carreño et al (2008),Mikulska et al (2011).…”
mentioning
confidence: 99%